Luther on Greek grammar - Oseka, Matthew (Vox Scripturae - Revista Teológica Internacional, 2025)
The present paper examines Luther’s command of Greek grammar in the context of grammatical compendia and lexica which were at his disposal. It also studies how Luther utilised grammatical insights of the church fathers and of the 15th- and 16th-century exegetes.